1995
DOI: 10.1159/000204089
|View full text |Cite
|
Sign up to set email alerts
|

Observation of T Cell Surface Antigens in the Clinical Course of Adult T-Cell Leukemia: Case Report of a Spontaneous Remission

Abstract: A patient with acute adult T-cell leukemia (ATL) in whom spontaneous remission was observed without any specific treatment having been given is described. The abnormal cell phenotype was CD4+, CD45RO+ and CD8-. As the number of abnormal cells decreased, CD4+ cell count decreased and CD8+ cells and CD45RA+ cells increased to normal levels (45 and 77%, respectively). Further, the number of cells with CD45RO antigen of intermediate fluorescence intensity increased. Five months after admission, we assessed the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…At present, there is no effective therapy for ATL. Although conventional chemotherapies do not appear to prolong the life of patients with ATL (Shimoyama et al, 1988;Shimoyama, 1991;Yamada et al, 2001), which is mainly caused by severe infection and drug resistance, spontaneous tumour regression has been described to occur in some ATL patients (Shimamoto et al, 1993;Kawabata et al, 2001), probably because of the immune response against ATL-associated antigens (Suzuki et al, 1995;Jinnohara et al, 1997). Recently, several studies have shown that allogeneic haematopoietic stem cell transplantation (allo-HSCT) could improve the prognosis of ATL patients Kami et al, 2003).…”
mentioning
confidence: 99%
“…At present, there is no effective therapy for ATL. Although conventional chemotherapies do not appear to prolong the life of patients with ATL (Shimoyama et al, 1988;Shimoyama, 1991;Yamada et al, 2001), which is mainly caused by severe infection and drug resistance, spontaneous tumour regression has been described to occur in some ATL patients (Shimamoto et al, 1993;Kawabata et al, 2001), probably because of the immune response against ATL-associated antigens (Suzuki et al, 1995;Jinnohara et al, 1997). Recently, several studies have shown that allogeneic haematopoietic stem cell transplantation (allo-HSCT) could improve the prognosis of ATL patients Kami et al, 2003).…”
mentioning
confidence: 99%
“…We reported a patient with acute type ATL who went into spontaneous remission and whose CD45RO-FI level was increased during the period of high disease activity and decreased during the phase in which spontaneous remission occurred (Suzuki et al, 1995). This clinical finding suggested that the CD45RO cells are involved in the immune surveillance mechanism in ATL patients.…”
Section: Discussionmentioning
confidence: 82%
“…Patients with acute type ATL who undergo spontaneous remission may represent a key to solving the problem. We describe a patient with acute type ATL who showed spontaneous remission and whose CD45RO expression on peripheral mononuclear cells (PBMC) changed in parallel with the clinical course from high disease activity to spontaneous remission (Suzuki et al, 1995). This finding suggests that the CD45RO antigen plays a role in the immune surveillance system in ATL patients.…”
mentioning
confidence: 95%
“…Since the first case of spontaneous regression of ATL in 1983, more than 20 patients have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Since the first case of spontaneous regression of ATL in 1983, more than 20 patients have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%